Direct Matching Antennas in RF Energy Harvesting Systems: A Review - Vahid Honarvar; Farzad Mohajeri (Majlesi Journal of Electrical Engineering)
A historical review of Radio Frequency Energy Harvesting (RFEH) Rectenna (Rectifier Antenna) Systems without a matching network is performed, with emphasis on the antenna part. As the antenna, matching network and rectifier are the main parts of the rectenna systems, the reasons behind the elimination of the matching network are presented and different special antennas suitable for direct matching to the rectifier, without using a matching network, are reviewed. Since the diode in the rectifier is a nonlinear element, its input impedance is changed with varying operating conditions such as input power, frequency and output load impedance of the rectifier. So, it is a challenge for researchers to match the antenna impedance directly to the rectifier in variable operational conditions.